Fragments Along the Way: Minimalism as an Account of Some Stages in First Language Acquisition - Goodluck, Helen; Kazanina, Nina (Frontiers in Psychology, 2020)
We take up three instances in which the minimalist model of syntax offers an account of children’s linguistic behaviour: 1) Merge can explain the two-word utterance stage in child language production and the subsequent stage involving utterances of variable length. 2) Errors in production of complex questions include the production of a middle copy of a question word (along the lines of ‘What did you see what Jane ate?’). This can be accounted for in terms of the child’s overt marking of a phase. 3) Differential rates with definite pronouns according to the structure in which the pronoun is contained. These phenomena all involve the combination of limited capacity production/comprehension systems with the syntactic component.